Щетконогий мотылек — Ostrinia scapulalis Walker (Lepidoptera, Pyraustidae) на Украине - Козакевич, З.М. (Вестник зоологии, 1978)
The Ostrinia Scapulalis Wlk. habitat in the Ukrainian region is considered and its area of distribution is described. A key to the inhabiting corn borers of the Ostrinia Hb. genus (O. palustralis, O. nubilalis, O. scapulalis, O. kasmirica) and the drawings of some their taxonomic characters are given. O. quadripunetalis S.V. is not found here.